DIGITAL ALTERNATIVES: MOBILE-CENTRIC CREATIVES - Venter, Anja (AoIR Selected Papers of Internet Research, 2015)
This paper describes the emerging creative ecologies of a group of young mobile-first creatives. These young South Africans come from contexts where they have had negligible exposure to the classical training or the resources that are deemed necessary for success in the world of visual design. Many have hacked informal mobile handset tools to produce instrumental visual designs that have directly helped them socially or economically. Yet the institutions where they are studying Extended Curriculum Programs in Visual Design do not recognize these ‘mobile-first’ visual design literacies. A post-colonial perspective offers an alternative framework to evaluate the dominant design aesthetics, and those that are privileged during formal design education. First, the paper takes an ethnographic viewpoint to tease out descriptions of the current media ecology amongst these participants based on a year of participant observation and 40 in-depth interviews; it investigates how these young people have used mobile technologies to navigate their lived realities through the production of visual design artifacts and participation on the "visual web". Through Participatory Design methods we developed the first iteration of a visual design application (“app”) for low-end smartphones called “Molio” – the mobile portfolio – based on the needs identified during the research process. We position our findings as an “implications for design” section that concludes the paper. We offer a call to action to artists, visual designers and developers to take the torch and explore mobile phones as a stand-alone design platform and learning aid for young aspiring designers.